Cold water immersion and recovery from strenuous exercise: a meta-analysis - Leeder, J.; Gissane, C.; van Someren, K.; Gregson, W.; Howatson, G. (British Journal of Sports Medicine, 2011)
Elite-level athletic training and competition is accompanied by the recovery of a series of physiological stressors. The physiological stress will vary considerably depending upon the specific exercise type, duration and intensity and also on the athletes' familiarisation to the exercise insult. It is well documented that when the exercise stress incorporates a novel eccentric component or the exercise is of considerable intensity or duration,1 athletes will likely experience numerous signs and symptoms of fatigue and cellular disturbance that have the potential to reduce performance. Physiological stress induced by intense exercise is associated with energy substrate depletion, hyperthermia, mechanical muscle damage, oxidative stress, inflammation and nervous system fatigue. The resulting symptoms manifest as reduced performance potential, likely due to increased muscle soreness and decreased muscle function,2 disturbed muscle position sense and reaction time3 as well as increased stiffness and swelling that can last for several days.4 The aetiology of reduced performance potential will vary depending upon the exact physiological stress being recovered from. For example, eccentric exercise is associated with a large mechanical stress and relatively low metabolic cost,5 whereas intermittent sprint exercise may involve both a large mechanical stress and a heightened metabolic cost.6 It is possible that the underlying time course of recovery between different exercise stressors is different, and this consequently may influence how recovery strategies could be implemented. For the purpose of this review, exercise will be subdivided into two categories: `eccentric exercise` that refers to the stress caused from exercise incorporating high mechanical stress (eg, eccentric contractions) and `high-intensity exercise` that refers to stress caused from exercise with a high metabolic cost as well as some elements of eccentric muscle contractions (eg, repeat sprint sports). Results: Fourteen studies meeting the inclusion criteria had data extracted for meta-analysis from an original search of 7 193. Participants` level of physical activity ranged from untrained to elite athlete groups, with a mean age of 23.2 ± 3.5 years. The total number of participants was 239 and the distribution of gender was not equal (male, n = 182; female, n = 57). The main fi ndings from the assessment of risk of bias in the included studies revealed that none of the included studies was able to effectively blind participants from the treatment.